Perbandingan Metode ARAS dan MOORA dalam Seleksi Penerimaan Pegawai Baru Non ASN - Susanto, Susanto; Ningrum, Setya; Cahyono, Yudi (STMIK Budi Darma, 2024)
The acceptance of new non-ASN candidates is a major problem in recruiting new employees, this happens because of the large number of new prospective employees who register and the number of vacancies that are inadequate, therefore research is carried out that aims to create a decision support system that can speed up the process of recruiting candidates. new employee. The methods used in this research are ARAS (Additive Ratio Assessment) and MOORA (Multi-Objective Optimization on the basis of Ratio Analysis) methods. The selection of this method is able to filter out the most alternatives based on weighting and this method is able to choose goals based on different criteria, namely benefits and costs. The results obtained from the ARAS method are the calculation rankings from the comparison of alternative utility functions with the optimal utility function values, while the results obtained from the MOORA method are the calculation rankings of the maximum and minimum values. From this value, an alternative that meets the criteria through calculations using the ARAS and MOORA methods, the employee alternative chosen is Yuniar Pilakso Angkasa with a final result of 0.935 for the ARAS method and 0.163 for the MOORA method. The results of the Spearman Rank coefficient test obtained a value of 0.9357% for the ARAS method and 0.7428% for the MOORA method, meaning that the two methods have a strong correlation level and can be used in recruiting new non ASN employees.